Off the mark : how grades, ratings, and rankings undermine learning (but don't have to) - Schneider, Jack (Writer on education); Hutt, Ethan L. (Harvard University Press, 2023)
"Today's regimes of testing and grading satisfy only the politicians who forced them on America's schools. Yet discarding assessment also serves students poorly. Off the Mark proposes an alternative, replacing motivation-killing tests and grading systems with well-designed assessment that accurately captures learning and fosters students' potential"-- Provided by publisher.
Keywords: Grading and marking (Students); Grading and marking (Students) -- United States.; Education -- Aims and objectives.; Learning.; Educational accountability.; Education and state -- United States.; Classement et notation (Élèves et étudiants); Classement et notation (Élèves et étudiants) -- États-Unis.; Apprentissage.; Responsabilité du rendement (Éducation); Éducation -- Politique gouvernementale -- États-Unis.; EDUCATION / Evaluation & Assessment; Education -- Aims and objectives; Education and state; Educational accountability; Learning; United States; Electronic books.